Pelatihan Good Manufacturing Practice (GMP) pada Usaha Pangan Binaan Universitas Andalas - Tivany Edwin; Reinny Patrisina; Alexie Herryandie Bronto Adi; Prima Fithri; Nindy Hidayah (Warta Pengabdian Andalas, 2020)
Food business is a very promising, but the products must be safe and worth buying. Good manufacturing practices (GMP) are production practices which considering various aspects, such as preventing food contamination during the production process, and production control as well. Small and Medium Enterprises (SME) fostered by Andalas University, which is engaged in the field of food manufacturing, wants to find its products better known and with a wide sales distribution. This can be realized if the business owner has the trust of many consumers. One effort that can be done is to implement the GMP For this reason, SMEs need to receive GMP Training.The method of this event is in the form of training to socialize the concept of GMP for food SMEs fostered by Andalas University, as well as self-assessment of the application of GMP that has been carried out by each SME. The training was held in the presence of 50 SMEs assisted by Andalas University, on Thursday / December 5, 2019 at Amaris Hotel, Padang. Participants were very enthusiastic in attending and actively participating during the training. Self assessment results showed most SMEs have not yet implemented a good GMP in their industry.